On total moduli of continuity for 2π-periodic functions of two variables in the space L_2,2 - Vakarchuk, M. B.; Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The description of the total moduli of continuity of 2π -periodic functions of two variables are obtained in the space L_2,2. The proposed description can be regarded as an extension of the famous results by O. V. Besov, S. B. Stechkin, V. A.Yudin on the moduli of continuity in L_2 in the two-dimensional case.